MRI Evaluation of Pregnant Women Presenting With Acute Abdominal Pain. (15th August 2017) - Moreno, Courtney C.; Alexander, Lauren F.; Sharma, Puneet; Mittal, Pardeep K.
Abstract : MRI is performed increasingly to evaluate pregnant women who present to the emergency department with acute abdominal pain. MRI provides a radiation-free alternative to CT and is less operator dependent than ultrasound. Our institution's protocol and the MRI appearance of common nonobstetric causes of acute abdominal pain are presented.